Chromosomal territory segmentation in apoptotic cells - Bártová, E; Jirsová, P; Fojtová, M; Soucek, K; Kozubek, S (Cellular and molecular life sciences, 2003)
The nuclear architecture of selected chromosomes in apoptotic nuclei of human leukemic cells K-562 and HL-60 was investigated. Etoposide and prolonged confluence were used for the induction of apoptosis. DAPI as well as TUNEL labeling of apoptotic nuclear bodies was combined with visualization of chromosomal territories by the FISH technique. Simultaneous vital staining by annexin V, propidium iodide, and Hoechst 33342 was applied to distinguish apoptotic, necrotic, and intact cell fraction of tested populations. Our FISH analyses revealed that the three-dimensional (3D) structure of apoptotic nuclei as well as the 3D structure of apoptotic bodies is preserved in formaldehyde-fixed cells. High-molecular-weight DNA fragmentation was determined in apoptotic K-562 cells in contrast to oligonucleosomal cleavage observed in apoptotic HL-60 cells. In K-562 populations, chromosomal territories were located separately either in one apoptotic body or underwent disassembly into chromosomal segments dispersed into single and/or several apoptotic bodies. The apoptotic disorganization of chromosomal territories was irregular, leading mainly to chromosomal segments of different sizes and, consequently, chromosomal disassembly was not observed at specific sites. In comparison with the control, an increased number of centromeric FISH signals were observed in prolonged confluence-treated K-562 cells induced to apoptosis. This finding can be explained either as a consequence of apoptosis or by polyploidization. Sequential staining of the same apoptotic nuclei by the FISH and TUNEL techniques revealed that chromosomal territory segmentation precedes the formation of nuclear apoptotic bodies.
Keywords: apoptóza; hybridizace in situ fluorescenční; lidé; K562 Cells; koncové značení zlomů DNA in situ; In Situ Hybridization, Fluorescence; DNA Fragmentation; buňky K562; Chromosome Aberrations; chromozomální aberace; In Situ Nick-End Labeling; Centromere; centromera; Apoptosis; fragmentace DNA; Humans